2019
DOI: 10.1093/omcr/omy127
|View full text |Cite
|
Sign up to set email alerts
|

Acute purulent pericarditis due co-infection with Staphylococcus aureus and Mycobacterium tuberculosis as first manifestation of HIV infection

Abstract: BackgroundPurulent pericarditis is an unusual first manifestation of HIV-infected patients. Co-infections in this scenario are possible and challenging. Mycobacterium tuberculosis is a frequent agent in purulent pericarditis related to HIV infection but co-infection with Staphylococcus aureus is rarely reported.Case presentationWe describe a rare case in otherwise asymptomatic 39-year-old diabetic man with acute purulent pericarditis leading to tamponade due to S. aureus and evidences of M. tuberculosis co-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Nevertheless, detection of two or more pathogens in the pericardial fluid as in our case is extremely rare. Two reported cases involved M. tuberculosis–Staphylococcus aureus and M. tuberculosis–Streptococcus pneumoniae coinfections in HIV-positive patients who presented with acute purulent pericarditis and cardiac tamponade [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, detection of two or more pathogens in the pericardial fluid as in our case is extremely rare. Two reported cases involved M. tuberculosis–Staphylococcus aureus and M. tuberculosis–Streptococcus pneumoniae coinfections in HIV-positive patients who presented with acute purulent pericarditis and cardiac tamponade [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus is a major opportunistic pathogen that reside mainly in the respiratory tract as well as on the skin ( Tong et al, 2015 ) and can cause a wide variety of clinical manifestations, such as Methicillin-resistant S. aureus (MRSA) infection ( Hassoun et al, 2017 ) and inflammatory response in the blood ( Labandeira-Rey et al, 2007 ). Serious clinical outcomes of S. aureus co-infection with Mtb had been reported ( Manigandan et al, 2013 ; Lamas et al, 2019 ). Lamas et al reported that S. aureus was co-infected with Mtb in a clinical case of primary purulent pericarditis ( Lamas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serious clinical outcomes of S. aureus co-infection with Mtb had been reported ( Manigandan et al, 2013 ; Lamas et al, 2019 ). Lamas et al reported that S. aureus was co-infected with Mtb in a clinical case of primary purulent pericarditis ( Lamas et al, 2019 ). Cadena et al found that the Staphylococcus genus was enriched in the Mtb-infected macaque based on 16S rRNA sequence analysis ( Cadena et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such avenues are clinically complicated, since affected patients can have co-infections caused by microbes belonging to different classes. For example, HIV patients can develop pericarditis in association with S. aureus and M. tb infections (Lamas et al, 2019). Similarly, myocarditis can result from coinfection with HHV-6 and parvovirus B19 (Rohayem et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of infectious and non-infectious triggers have been implicated in the causation of pericarditis ( (Brucato et al, 2008). The disease can also arise from co-infections caused by multiple organisms such as S. aureus and M. tb in immune-suppressive individuals as might occur in HIV infection imposing a clinical challenge to target specific pathogens for therapy particularly in patients with recurrences (Lamas et al, 2019).…”
Section: Pericarditismentioning
confidence: 99%